Global productivity, international collaborations, and research trends in chronic spontaneous urticaria: A bibliometric overview - Hugo W.F. Mak, MBBS, MRes(Med); Freya K.L. Chung, MBBS; Philip H. Li, MD; Marcus Maurer, MD (Journal of Allergy and Clinical Immunology: Global)
Background: The treatment of chronic spontaneous urticaria (CSU) remains a challenge despite novel therapies such as omalizumab. With growing international interest in research on CSU, a comprehensive review of the global productivity, collaborations, and trending topics in CSU research may help inform future directions in patient management. Objectives: This study aims to outline the trends in CSU research by using bibliometric analysis, focusing specifically on global productivity, collaborative efforts, and emerging research topics spanning from 1977 to 2023. Methods: Publications related to CSU, including original articles, reviews, and letters, were sourced from the Web of Science Core Collection, and statistical analyses were performed using the Bibliometrix package in R and IBM SPSS Statistics. Results: A total of 2940 publications from 77 countries were analyzed. CSU research activity has increased exponentially since 2010, with more than half of the publications (50.2% [1477 of 2940]) published since 2016. These publications appeared in allergy, immunology, and dermatology journals led predominantly by European, Asian, and American researchers. International collaborations rose from 11.3% to 22.2%. Shifts in research focus, such as a shift in treatments from antihistamines to omalizumab, and growing emphasis on quality of life were noted. Conclusion: This study revealed a dynamic and increasingly collaborative CSU research landscape, emphasizing the need for continuous global partnerships to enhance treatment outcomes and improve patients’ quality of life. Challenges regarding access to advanced therapies persist, highlighting the importance of expanding international collaborations and inclusive research practices.